Context of work and elements of risk faced by waste pickers from the Cancharani sanitary landfill, Puno, Peru //Contexto de trabajo y elementos de riesgo que enfrentan los recicladores del botadero sanitario de Cancharani, Puno, Perú - Ticona-Carrizales, Lucio; Ferro Gonzales, Polan Franbalt; Maquera-Luque, Pedro Jesús; Apaza-Panca, Cynthia Milagros (Revista de la Universidad del Zulia, 2020)
Abstract The study was carried out in the sanitary landfill of Puno, from December 2017 to January 2018 and aimed to determine the relationship between working conditions and the risk factors faced by waste pickers from the Cancharani sanitary landfill, Puno-Peru. The methodology applied corresponds to the transversal correlational design, with a census-type study sample. The statistical tests applied were the Spearman correlation test and the Mann Whitney U test. The results indicate that there is no correlation (r = 0.102; α = 0.01), between working conditions and the risk factors that workers face. With regard to gender, it was found that women admit the inadequate working conditions in which they work (U = 60.00), considering that they are the same who manipulate solid waste from dangerous places such as pharmacies and others without optimal protection. On the other hand, men are the ones who perceive more the risk factors they face (U = 50.00) and are the ones who handle the waste coming from the homes. According to the age ranges, it was obtained that those aged 18 to 29 identify and perceive the inadequate working conditions in which they work (RP = 96.50). Likewise, it is those of this age range who identify the risk factors to which they are subject (PR = 91.00). We can conclude that the work situations and the risk factors are not significantly related. Resumen El estudio se llevó a cabo en el relleno sanitario de Puno, periodo 2017-2018, y tuvo como objetivo determinar la relación entre las condiciones de trabajo y los factores de riesgo que enfrentan los recicladores del relleno sanitario de Cancharani, Puno, Perú. Se basó en un diseño correlacional transversal, con una muestra de estudio tipo censo. Las pruebas estadísticas aplicadas fueron la prueba de correlación de Spearman y la prueba U de Mann Whitney. Los resultados indican que no hay correlación (r = 0.102; α = 0.01), entre las condiciones de trabajo y los factores de riesgo que enfrentan los trabajadores. Con respecto al género, se encontró que las mujeres admiten las condiciones de trabajo inadecuadas en las que trabajan (U = 60.00), considerando que son las mismas que manipulan los desechos sólidos de lugares peligrosos como farmacias y otros sin una protección óptima. Por otro lado, los hombres son los que perciben más los factores de riesgo que enfrentan (U = 50.00) y son los que manejan los desechos provenientes de los hogares. De acuerdo con los rangos de edad, se obtuvo que las personas de 18 a 29 años identifican y perciben las condiciones de trabajo inadecuadas en las que trabajan (RP = 96.50). Asimismo, son los de este rango de edad quienes identifican los factores de riesgo a los que están sujetos (PR = 91.00). Podemos concluir que las condiciones de trabajo y los factores de riesgo no están significativamente relacionados.